2020
DOI: 10.1186/s13722-020-00186-7
|View full text |Cite
|
Sign up to set email alerts
|

Six-month retention and changes in quality of life and substance use from a low-threshold methadone maintenance therapy programme in Durban, South Africa

Abstract: Background: Emerging data points to a potential heroin use epidemic in South Africa. Despite this, access to methadone maintenance therapy and other evidence-based treatment options remains negligible. We aimed to assess retention, changes in substance use and quality of life after 6 months on methadone maintenance therapy provided through a low-threshold service in Durban, South Africa. Methods:We enrolled a cohort of 54 people with an opioid use disorder into the study. We reviewed and described baseline soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 50 publications
0
9
1
Order By: Relevance
“…Instead, they were encouraged to re-join the project, following a medical assessment and discussion with the clinical and psychosocial team. Retention at 6 months was 81%, with a significant reduction in heroin use and a significant improvement in mental health [56]. At 12 months, retention was 74%, with notable improvements in participants' quality of life [56].…”
Section: South Africa's First Low-threshold Opioid Agonist Therapy Prmentioning
confidence: 95%
“…Instead, they were encouraged to re-join the project, following a medical assessment and discussion with the clinical and psychosocial team. Retention at 6 months was 81%, with a significant reduction in heroin use and a significant improvement in mental health [56]. At 12 months, retention was 74%, with notable improvements in participants' quality of life [56].…”
Section: South Africa's First Low-threshold Opioid Agonist Therapy Prmentioning
confidence: 95%
“…(30) However, small pilot studies have shown high retention rates, opiate reduction, and improvement in mental health in individuals accessing methadone treatment in South Africa. (31) Nevertheless, the lack of routine hepatitis C testing and access to PrEP indicate significant gaps in service delivery. Integration of harm reduction services into routine healthcare could impact the rising use of opiates and the HIV epidemic in South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of OUD with OAMT as part of a larger care package is supported by strong evidence globally and in South Africa (Gloeck, Harris, Webb, & Scheibe, 2020;Scheibe, Shelly, Gerardy, et al, 2020;Lize Weich, 2010;WHO, 2004). Long term use of OAMT (≄ 6 months) is associated with reduced dependence, reduced morbidity, and mortality from infectious diseases, reduced criminal behaviour, improved physical and psychological health and better social integration and functioning (Gloeck et al, 2020).…”
Section: Discussionmentioning
confidence: 99%